Deep Neck Abscesses in Children: An Italian Retrospective Study. Issue 12 (25th December 2021) - Donà, Daniele; Gastaldi, Andrea; Campagna, Marta; Montagnani, Carlotta; Galli, Luisa; Trapani, Sandra; Pierossi, Nicola; De Luca, Maia; D'Argenio, Patrizia; Tucci, Filippo Maria; De Vincentiis, Giovanni; Grotto, Paolo; et al.
Abstract : Background: Retropharyngeal and parapharyngeal abscesses (RPAs, PPAs) usually affect young children. Surgical drainage and/or antibiotic therapy are treatment of choice, but no specific guidelines exist. In order to reduce the risk of severe complications, appropriate diagnosis and therapy are necessary. The aims of the study were to review diagnosis and management of children with RPAs/PPAs and to compare surgical versus medical approach. Methods: This is a multicenter retrospective study including all patients younger than 15 years admitted at 4 Italian pediatric hospitals of Florence, Padua, Rome, and Treviso, with International Classification of Diseases, Ninth Revision discharge diagnosis code of RPAs and PPAs, from January 1, 2008, to December 31, 2016. Results: One hundred fifty-three children were included. The median age was 4.4 years, with overall male predominance. Heterogeneous signs and symptoms (fever, neck cervical, lymphadenopathy, pain, and stiff neck most frequently) and a large mixture of bacteria from pus cultures were detected. Computer tomography (66.7%) and magnetic resonance imaging (27.5%) were performed to confirm the presence of abscess. Fifty-one percent of abscesses were greater than 3 cm. Eighty-seven patients (56.9%) underwent surgery, and 66 (43.1%) were treated with antibiotics alone (mostly ceftriaxone, metronidazole, amikacin, and clindamycin) with median days of therapy of 26.5 days and length of therapy of 16.0 days of median. Median length of stay was 11 days. None had severe complications. Multivariate analysis indicated as independent predictive factors of surgery abscess of 3 cm or greater, high white blood cell count, and—most of all—the hospital of admission. Conclusions: Deep neck abscesses mostly affect patients in early childhood, with a combination of nonspecific signs and symptoms, and it still emerges as a heterogeneous approach in diagnosis and management of these infections. Thus, common shared protocols represent an essential tool in order to standardize care and improve patients' outcomes.